Levels of cassava residue in diets for growing and finishing pigs - Bertol, Teresinha Marisa; Lima, Gustavo Julio Mello Monteiro de (Pesquisa Agropecuaria Brasileira, 1999)
Two experiments were conducted in order to evaluate the inclusion of cassava residue (RIFM) in diets for growing and finishing pigs. In the first experiment, four levels (0, 6.67, 13.33 and 20%) of RIFM in growing diets were studied. The inclusion of RIFM in the diets caused a cubic effect on average daily gain (GPMD, P < 0.01, R2 =0.80, y=804-54.06x+6.03x2-0.19x3) and final body weight (PMFC, P<0.01, R2 =0.79, y=60.47-2.87x+0.33x2-0.01x3) and a linear effect on average daily intake (CRMD, P < 0.04, R2 = 0.74, y=2090-136x). The quadratic effect was significant for slaughter body weight (PMA, P < 0.05, R2 = 0.69, y=98.88-1.28x+0.05x2) . In the second experiment, RIFM was studied in four levels (0, 10, 20 and 30%) of inclusion in diets for finishing pigs. Pig performance was not affected (P > 0.10) by the inclusion of any level of RIFM. It was concluded that the inclusion of RIFM in diets for growing pigs, in levels like 6.67% or higher, decrease swine performance. In the finishing phase, the performance is not affected by the inclusion of any levels of RIFM, up to 30%.